Implementation of the Contextual Teaching and Learning Approach to Improve the Mathematical Literacy Skills of Phase D Students of Class IX1 of SMPN 4 Tambang - Arnela Marwita; Armis Armis; Sakur Sakur (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Students' poor mathematical literacy, particularly when it comes to the content of Two-Variable Linear Equation Systems (SPLDV), which calls for the ability to comprehend information, model it mathematically, and clearly communicate the solution's findings, is what spurred this study. This project intends to improve the learning process and increase students' mathematical literacy skills by using the Contextual Teaching and Learning (CTL) approach. Using the Classroom Action study (CAR) methodology created by Kemmis and McTaggart, the research was carried out in two cycles. Thirty students from SMP Negeri 4 Tambang's class during the even semester of the 2024–2025 school year served as the study subjects. Mathematical literacy competency tests and teacher and student activity observations were used to gather research data in the form of descriptions. The results of the study indicate that the application of CTL is able to improve the implementation of learning, marked by increased student activeness in asking questions, discussing, and expressing opinions, as well as a more consistent role of teachers as facilitators. In terms of learning outcomes, students' mathematical literacy skills improved from cycle I to cycle II, both in writing problem information, using appropriate concepts and procedures, and in drawing conclusions from solutions. Thus, it can be said that using CTL effectively raises the quality of mathematics instruction while also helping students become more mathematically literate while using the SPLDV content.